MODEL OF INTEGRATED ASSESSMENT LAYER FOR IMPLEMENTATION READINESS OF BLOCKCHAIN-BASED TRACEABILITY SYSTEM - Pradana, I Gusti Made Teddy; Djatna, Taufik; Hermadi, Irman; Yuliasih, Indah (Jurnal Teknologi Industri Pertanian, 2024)
Amid the development of blockchain technology in various sectors, this research proposes a novel Integrated Assessment Model to evaluate readiness for implementing blockchain-based systems. This research was carried out in stages using a modified project evaluation system approach, which includes a series of processes such as systematic literature review, observation and interviews, and case study assessment using BDD and SEM-PLS. A comprehensive literature review reveals several important areas for assessing blockchain technology adoption readiness: technical maturity, domain suitability, regulatory landscape, and stakeholder dynamics. Based on these findings, the proposed model is organized into five layers: technology, business, data, regulations, and user interface. As a follow-up research on the development of analysis and design of a blockchain-based traceability system in Kintamani coffee, BDD confirmed stakeholder engagement. In addition, user readiness to change using a blockchain-based system is determined primarily by technology compatibility (TC) based on SEM-PLS and IPMA results. The main contribution of this research is to blockchain adoption by proposing a comprehensive and practical framework - the Integrated Assessment Model. It is recommended that future research be directed at developing models for more specific case contexts, expanding suitability for emerging blockchain frameworks, focusing on specific regions, and longitudinal research in terms of adoption trends and barriers. Keywords: assessment model, implementation readiness, blockchain, traceability system, agri-food supply chains